Integrasi Artificial Intelligence sebagai Inovasi Perancangan Perangkat Pembelajaran dan Asesmen Guru IPA - Ryan Ardiansyah; Purwati Kuswarini Suprapto; Rita Fitriani; Dea Diella; Herni Yuniarti Suhendi (Universitas Hamzanwadi, 2025)
The rapid development of artificial intelligence (AI) offers great potential to enhance the quality of education, particularly in supporting the implementation of the Merdeka Curriculum. This community service program aimed to improve teachers’ competencies in utilizing AI, specifically ChatGPT and GEMINI, to develop innovative learning tools. The training and mentoring activities were conducted at SMPN 1 Singaparna, Tasikmalaya Regency, involving 26 science teachers. Evaluation was carried out through pretests and posttests to measure participants’ knowledge improvement, workshops to produce learning products, and monitoring of classroom implementation. Pretest results showed that 65% of participants had a low understanding of AI concepts and the Merdeka Curriculum. After the training, 85% demonstrated good understanding. The workshop produced 10 AI-based learning tools that were assessed as innovative, relevant, and creative. Monitoring indicated that 75% of participants successfully integrated these tools into their classroom practices. This success was influenced by hands-on training, continuous mentoring, and teacher collaboration. However, some participants still faced challenges in adapting the tools to individual student needs. The program demonstrates that collaborative practice-based training and mentoring effectively enhance teacher competencies and foster the creation of technology-based learning innovations aligned with the demands of the Merdeka Curriculum.